PRP19: a novel spliceosomal component. - Cheng, S C (1993)
We have isolated the gene of a splicing factor, PRP19, by complementation of the temperature-sensitive growth defect of the prp19 mutant of Saccharomyces cerevisiae. The gene encodes a protein of 502 amino acid residues of molecular weight 56,500, with no homology to sequences in the data base. Unlike other PRP proteins or mammalian splicing factors, the sequence of PRP19 has no discernible motif. Immunoprecipitation studies showed that PRP19 is associated with the spliceosome during the splicing reaction. Although the exact function of PRP19 remains unknown, PRP19 appears to be distinct from the other PRP proteins or other spliceosomal components.